Facing Sender States: Russia’s Smart Power and Energy Security Strategy to Survive from Sanctions 2022-2023 - Maruti, Ayu; Maharani, Gita Ardya; Arisanto, Puguh Toko (Jurnal Ilmiah Hubungan Internasional Fajar, 2024)
This paper aims to explain Russia's efforts to face sender states for Russia’s invasion of Ukraine since February 2022. Including EU countries, the US and its alliances, sender states have gradually imposed various economic sanctions on Russia as target state ranging from freezing state and individual assets to cutting off import and export activities aimed at halting Russia's invasion. Russia, in the aftermath of this, experienced various problems, in particular energy sector as top commodities yet Russia economy has not collapsed. As smart power (regarded as a combination of hard and soft power) and energy security as frameworks are proposed, authors seek to analyze how Russia deals with and survives from the economic sanctions. Previous studies have not addressed how Russia's efforts to deal with economic sanctions examined from the two concepts, thus this article seeks to fill the gap. Using qualitative research methods and the two concepts, authors found that Russia only employed hard power as coercive actions to deal with sender states through a bunch of energy and non-energy instruments. Russia, one of the largest energy exporters and regarding energy security strategy, has undertaken three strategic aspects; energy source sovereignty, foreign market access and financial security for investment. Keywords: Sender States, Economic Sanctions, Russia, Smart Power, Energy Security